+0  
 
-1
27
1
avatar+251 

6x+c=k for x 

 

A:x=  k- c/6

 

B. x=6 (k-c)

 

C.x=6(k+6)

 

D. x= k+c/ 6

 Mar 1, 2019

Best Answer 

 #1
avatar+215 
+3

A. Divide both sides by 6, and you get \(x +\frac c6 = \frac k6\) . Subtract \(\frac c6\) from both sides and you end up with \(x = \frac {k-c}{6}\)

.
 Mar 1, 2019
 #1
avatar+215 
+3
Best Answer

A. Divide both sides by 6, and you get \(x +\frac c6 = \frac k6\) . Subtract \(\frac c6\) from both sides and you end up with \(x = \frac {k-c}{6}\)

LagTho Mar 1, 2019

11 Online Users

avatar